2015
DOI: 10.5606/kbbihtisas.2015.53138
|View full text |Cite
|
Sign up to set email alerts
|

Is the time from the onset to the treatment a prognostic indicator for hearing recovery in idiopathic sudden sensorineural hearing loss?

Abstract: Our study results suggest that treatment outcomes are better in the patients presenting to hospital at an early stage of loss of hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
1
0
1
Order By: Relevance
“…Chung et al performed a multivariate analysis of the prognostic factors of SSNHL and found that early treatment was associated with a good prognosis ( 6 ). Our study found that treatment onset time was an independent risk factor affecting the prognosis of SSNHL with the profound audiogram pattern, consistent with previous studies ( 2 , 9 , 27 ). This may be related to the microcirculation disorder of the inner ear.…”
Section: Discussionsupporting
confidence: 93%
“…Chung et al performed a multivariate analysis of the prognostic factors of SSNHL and found that early treatment was associated with a good prognosis ( 6 ). Our study found that treatment onset time was an independent risk factor affecting the prognosis of SSNHL with the profound audiogram pattern, consistent with previous studies ( 2 , 9 , 27 ). This may be related to the microcirculation disorder of the inner ear.…”
Section: Discussionsupporting
confidence: 93%
“… 16 Uysal et al studied 96 ISHL patients and reported better recovery rates when the treatment began within the first week. 17 Similarly, Cho et al found significantly higher recovery rates (88%) in patients who were treated within the first 3 days. 18 Contradicting results are also present in the literature.…”
Section: Discussionmentioning
confidence: 90%
“…6,7) 현재까지 알려진 성인 돌발성 난청의 예후에 미치는 인자 는 청력저하 발생 후 치료까지 걸린 시간, 동반증상 유무, 기저 질환 유무, 초기 청력 저하 정도 등으로 알려져 있다. 8) 성인의 돌발성 난청과 달리 소아 돌발성 난청은 빈도가 적 고 예후가 불량한 것으로 여겨지며, 특히 10세 이하에서는 10 세 초과의 소아에 비해 더욱 치료결과가 나쁘다는 보고가 있 다. 9,10)…”
unclassified